1991
DOI: 10.1093/jnci/83.13.951
|View full text |Cite
|
Sign up to set email alerts
|

A Follow-up Study of Colonic Epithelial Proliferation as a Biomarker in a Native-American Family with Hereditary Nonpolyposis Colon Cancer

Abstract: A 7-year follow-up study of colonic mucosa proliferation markers was conducted on members of a Native-American family with hereditary nonpolyposis colon cancer. Reproducibility of a tritiated thymidine autoradiography assay for labeling indexes during this 7-year biologically significant time frame was established. A good correlation between tritiated thymidine and a newer technique, bromodeoxyuridine immunoperoxidase staining, was seen. No confounding effect could be attributed to standard colon preparation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…2' 22273031 Finally, our data donfirm the longitudinal stability of the kinetic markers (both total labelling index and compartmental distribution of labelled cells) over time. This finding is in agreement with those of Lynch et al 39 Furthermore, in dietary trials aimed at reducing the risk of colon cancer in which these parameters were repeatedly evaluated, the same stability has been noted in control patients.424345 1 If more extensive studies confirm our belief that markers of proliferative activity are reliable predictors of polyp recurrence, the initial kinetic pattern can be used to individualise follow up protocols for polypectomy patients, eliminating unnecessary colonoscopy for those who are unlikely to suffer recurrence and increasing surveillance in those with recidivant tendencies.…”
Section: Discussionsupporting
confidence: 94%
“…2' 22273031 Finally, our data donfirm the longitudinal stability of the kinetic markers (both total labelling index and compartmental distribution of labelled cells) over time. This finding is in agreement with those of Lynch et al 39 Furthermore, in dietary trials aimed at reducing the risk of colon cancer in which these parameters were repeatedly evaluated, the same stability has been noted in control patients.424345 1 If more extensive studies confirm our belief that markers of proliferative activity are reliable predictors of polyp recurrence, the initial kinetic pattern can be used to individualise follow up protocols for polypectomy patients, eliminating unnecessary colonoscopy for those who are unlikely to suffer recurrence and increasing surveillance in those with recidivant tendencies.…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, Navajo kindreds with hereditary nonpolyposis CRC syndrome have been followed for decades. 38 Further work is needed in these populations to elucidate CRC risk factors and to assess whether CRC screening recommendations should be modified to include younger individuals.…”
Section: Discussionmentioning
confidence: 99%
“…59,66 Several studies have demonstrated increased proliferation in normal or uninvolved tissues in patients with familial history or hereditary CRC. 13,34,54 The increased proliferation and genetic alterations (eg, KRAS2) observed in mucosa distant from CRC suggest the controversial idea that ''normal'' epithelium undergoes specific premalignant changes (the ''field effect'') rendering it prone to malignancy. 11,42,60 Changes could result from paracrine signaling from malignant cells or colonization of much of the colorectal epithelium by a clonal expansion.…”
Section: Discussionmentioning
confidence: 99%